Effects of Soil Structure Interaction on Strength Reduction Factors - Eser, M.; Aydemir, C.; Ekiz, I. (ELSEVIER SCIENCE BV, 2011)
In this study, strength reduction factors for SDOF systems of period range of 0.1-3.0 s. with elastoplastic behavior are obtained for 20 earthquake motions recorded on soft soils considering soil structure interaction. Soil structure interacting systems are modeled with effective period, effective damping and effective ductility values differing from fixed-base case. For inelastic time history analyses, Newmark method for step by step time integration was adapted in an in-house computer program. Results are compared with those calculated for fixed-base case. It is concluded that soil structure interaction reduces strength reduction factors for soft soils, therefore, using the. xed-base strength reduction factors for interacting systems lead to non-conservative design forces. (C) 2011 Published by Elsevier Ltd.
Keywords: Soil-structure interaction; strength reduction factors; time-history analysis; ductility demand; Construction & Building Technology; Engineering